2019
DOI: 10.3390/rs11232842
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of ASCAT Radar Scatterometer Observations Over Land: A Case Study Over Southwestern France

Abstract: This paper investigates to what extent soil moisture and vegetation density information can be extracted from the Advanced Scatterometer (ASCAT) satellite-derived radar backscatter (σ°) in a data assimilation context. The impact of independent estimates of the surface soil moisture (SSM) and leaf area index (LAI) of diverse vegetation types on ASCAT σ° observations is simulated over southwestern France using the water cloud model (WCM). The LAI and SSM variables used by the WCM are derived from satellite obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…where A, B, C, D, V 1 and V 2 are parameters of the WCM model. The two latter ones represent the effect of the vegetation on the radar backscattering [74]. In the original formulation of the WCM, V 1 equals to 1 [43].…”
Section: Vod From Active Microwave Observationsmentioning
confidence: 99%
“…where A, B, C, D, V 1 and V 2 are parameters of the WCM model. The two latter ones represent the effect of the vegetation on the radar backscattering [74]. In the original formulation of the WCM, V 1 equals to 1 [43].…”
Section: Vod From Active Microwave Observationsmentioning
confidence: 99%
“…LDAS-Monde would benefit from having observations linked to vegetation available every day. This is the case of radar backscatter coefficients as shown by Lievens et al (2017) and Shamambo et al (2019) https://doi.org/10.5194/hess-2019-391 Preprint. Discussion started: 20 August 2019 c Author(s) 2019.…”
Section: Discussionmentioning
confidence: 97%
“…It raises the question of the quality of ISBA and/or SSM observations (after seasonal linear rescaling) in arid places. Stoffelen et al (2017) have shown that observed SSM derived from scatterometers can have poor quality in arid places. Further studies of such aspects are beyond the scope of this paper.…”
Section: Impact Of Assimilation On Ssmmentioning
confidence: 99%